2021
DOI: 10.1002/jlb.3ma0521-742rrr
|View full text |Cite
|
Sign up to set email alerts
|

The imbalance of Th17/Treg via STAT3 activation modulates cognitive impairment inP. gingivalis LPS-induced periodontitis mice

Abstract: Periodontitis is one of the most common oral diseases worldwide, and it is associated with various systemic diseases, including cognitive diseases. STAT3 regulates the inflammatory cascade and influences adaptive immunity by modulating Th17/Treg cell differentiation. In this study, we aimed to explore the effect of adaptive immunity inside and outside the brain on the association between periodontitis and cognitive impairment and understand the role of the STAT3 signaling pathway. We established Porphyromonas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 53 publications
(105 reference statements)
2
27
0
Order By: Relevance
“…Recently, it has been shown that a particular subset of Tfh cells infiltrate the brain of mice suffering systemic lupus erythematosus, thereby possibly contributing to the neuropsychiatric manifestations (memory impairment, cognitive deficits and mood disturbance) of this disease (80). Some of these symptoms are also present in anxiety, mood and trauma and stress-related disorders (81).…”
Section: Findings In Non-human Primatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that a particular subset of Tfh cells infiltrate the brain of mice suffering systemic lupus erythematosus, thereby possibly contributing to the neuropsychiatric manifestations (memory impairment, cognitive deficits and mood disturbance) of this disease (80). Some of these symptoms are also present in anxiety, mood and trauma and stress-related disorders (81).…”
Section: Findings In Non-human Primatesmentioning
confidence: 99%
“…Even if the use of ligatures to induce periodontitis has demonstrated more severe periodontal destruction in shorter time, oral gavages with periodontal pathogens or their endotoxins (such as LPS) are more representative of the physiopathology of periodontitis (84). LPS-induced periodontitis may promote the occurrence and progression of learning and memory impairment by modulating the T helper 17 (Th17)/regulatory T cell (Treg) balance in a mechanism related to the STAT3 signaling pathway (81). In a similar way, C57BL/6 mice injected with P. gingivalis exhibited impaired spatial learning and memory during the Morris Water Maze test and exhibited attenuated passive avoidance learning, effects that were mediated by the activation of the toll-like receptor (TLR) 4 pro-inflammatory signaling pathway (85).…”
Section: Findings In Rodentsmentioning
confidence: 99%
“…Other subsets of T regs were defined based on cell phenotype and characteristic markers, secreted cytokines and chemokines and specific immune regulation functions ( Table 1 ) ( 43 , 48 ). These include Resting T regs (rT regs ), Activated T regs (aT regs ), Non-suppressive T regs (non-T regs ) and helper-like T regs (Th-T regs ), and three recently discovered Foxp3-T regs .…”
Section: Sae and Regulatory T Cellsmentioning
confidence: 99%
“…Based on their origin, T regs can be divided into two subsets: thymus-derived T regs (tT regs ) and peripheral-derived T regs (pT regs ) (40)(41)(42)(43). tT regs (44) are characterized by their constitutive expression of Foxp3 and stable suppressive function, whereas pT regs (45) exhibit unstable Foxp3 expression, unstable suppressive function and can differentiate into cells with an effector function.…”
Section: Sae and Regulatory T Cellsmentioning
confidence: 99%
See 1 more Smart Citation